Evaluation of a laboratory-scale vertical flow filter bed using coco peat as sorbent material to remove copper in aqueous solution - Espiritu, Danilyn D.C (2012)
Coco peat, a waste by-product of coco coir processing, is abundantly available in the Philippines. Several batch experiments on coco peat's efficiency to remove heavy metals from aqueous solution have been completed and these showed that the coco-peat is a good sorbent material. This study introduces coco peat as a sorbent material in a vertical flow filter bed to treat wastewater containing copper ions. A laboratory-scale vertical flow filter bed with an are of 2.44 sq.m and a total height of 1.1m was constructed to treat wastewater containing copper solutions with concentrations of 25ppm and 50ppm. It was operated for five months. The system has established a minimum value of 98.88% copper removal which occurred on the 21st week of operation. Investigation of the coco peat concentration-depth profile showed that copper concentration was high at the upper 0.03m layer of coco peat bed and decreases through the depth. This high percentage removal and high copper contaminant retained in the coco peat bed layer showed that coco peat is an efficient sorbent material in a vertical flow system to treat copper in wastewater. Using Hydrus, numerical modelling was applied to simulate the contaminant transport of dissolved heavy metals in the coco peat filter bed using different variables such as type and concentration of contaminant, reactor size, substrate depth, and pore volumes.